New insights from GWAS for the cleft palate among han Chinese population - Duan, Shi-Jun (Med Oral Patol Oral Cir Bucal, 2017)
BACKGROUND: Genome wide association studies (GWAS) already have identified tens of susceptible loci for nonsyndromic cleft lip with or without cleft palate (NSCL/P). However, whether these loci associated with nonsyndromic cleft palate only (NSCPO) remains unknown. MATERIAL AND METHODS: In this study, we replicated 38 SNPs (Single nucleotide polymorphisms) which has the most significant p values in published GWASs, genotyping by using SNPscan among 144 NSCPO trios from Western Han Chinese. We performed the transmission disequilibrium test (TDT) on individual SNPs and gene-gene (GxG) interaction analyses on the family data; Parent-of-Origin effects were assessed by separately considering transmissions from heterozygous fathers versus heterozygous mothers to affected offspring. RESULTS: Allelic TDT results showed that T allele at rs742071 (PAX7) (p=0.025, ORtransmission=3.00, 95%CI: 1.09-8.25) and G allele at rs2485893 (10kb 3’ of SYT14) were associated with NSCPO (p=0.0036, ORtransmission= 0.60, 95%CI: 0.42-0.85). Genotypic TDT based on 3 pseudo controls further confirmed that rs742071 (p-value=0.03, ORtransmission=3.00, 95%CI: 1.09-8.25) and rs2485893 were associated with NSCPO under additive model (p-value= 0.02, ORtransmission= 0.66, 95%CI: 0.47-0.92). Genotypic TDT for epistatic interactions showed that rs4844913 (37kb 3’ of DIEXF) interacted with rs11119388 (SYT14) (p-value=1.80E-08) and rs6072081 (53kb 3’ of MAFB) interacted with rs6102085 (33kb 3’ of MAFB) (p-value=3.60E-04) for NSCPO, suggesting they may act in the same pathway in the etiology of NSCPO. CONCLUSIONS: In this study, we found that rs742071 and rs2485893 were associated NSCPO from Han Chinese population; also, interactions of rs4844913:rs11119388 and rs6072081:rs6102085 for NSCPO were identified, gene-gene interactions have been proposed as a potential source of the remaining heritability, these findings provided new insights of the previous GWAS. Key words:GWAS, NSCPO, TDT, parent-of-origin effects, epistatic interactions.